Nicked-sleeve interface for two-dimensional capillary electrophoresis - Flaherty, Ryan J. (2013)
We report an improved interface for two-dimensional capillary electrophoresis. This interface is based on capillary tubing and a Plexiglas chip, both of which were milled using a micro-dicing saw. The interface was evaluated and compared to a traditional interface design for both pseudo one-dimensional and two-dimensional capillary electrophoresis. We observe less than 70% transfer efficiency for the traditional design and greater than 90% transfer efficiency with this new interface.